THE IMPLICATIONS OF SOLAR PANELS TOWARDS CRIME PREVENTION IN THE UNIVERSITY OF LIMPOPO - Mahlodi Daniel Raphiri; Michael Nkosinathi Khwela; Mohale Ernest Selelo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The purpose of this paper is to conceptually analyse and demonstrate the implications of solar panels towards crime prevention in the University of Limpopo. It argues that the development of solar panels as a strategy for the University of Limpopo can increase and reduce criminal incidents, and for the campus to save costs and supply renewable energy sources to the community of Mankweng. Crime in South Africa has been an issue of contention in institutions of higher learning, businesses, and the society at large. This article examines the factors behind the implications of solar panels towards crime prevention, role of solar panels in crime deterrence and implementation of solar panels influences safety and control. Furthermore, the paper underscores the potential outcomes of this trend on student-staff safety and the environment. The concern is great deal on criminal incidents within the University of Limpopo that occur at night during loadshedding. This leads to robbery, break-ins, rape and other criminal activities that occurs at night during power cuts. As a result, it is not a shock that most students on campus struggle to keep up with their academic workload during loadshedding at night and leaves student accommodation vulnerable in dark hours. It is evident that solar panels offer a clean and abundant source of power. This is a conceptual paper that depends heavily on qualitative approach to conceptually demonstrate the implications of solar panels towards crime prevention in the University of Limpopo which ultimately threatens student-staff safety. Hence, this paper recommends that the installation of solar panels in all institutions of higher learning would ultimately assist in curbing some of the criminal elements not only in the University of Limpopo.